Distress and body image disturbances in women with breast cancer in the immediate postsurgical period: The influence of attachment insecurity. (December 2016) - Favez, Nicolas; Cairo Notari, Sarah; Charvoz, Linda; Notari, Luca; Ghisletta, Paolo; Panes Ruedin, Bénédicte; Delaloye, Jean-François
The aim of this study was to assess, in the immediate postsurgical period, the influence of attachment avoidance and anxiety on distress and body image disturbances in women facing breast cancer. Seventy-five women participated in the study 3 weeks after surgery. Questionnaires were used to assess study variables. To predict distress and body image disturbances, we controlled for several variables known to influence adjustment to the stress of breast cancer. The results of hierarchical regression analyses show that attachment explains the outcomes above and beyond other influential variables. Insecurely attached women are especially vulnerable to the stress of the disease.